RADIOGRAPHIC DETERMINATION OF THE DIFFICULTY IN EXTRACTION OF THE THIRD IMPACTED MANDIBULAR MOLARS - Sorana Maria Bucur; Dorin Ioan Cocoș; Alexandra-Camelia Po; Mariana Păcurar; Carmen Galea (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study: to evaluate a reliable and user-friendly index to predict the surgical difficulty of the extractions of mesioangular impacted mandibular third molars. Material and method: Our retrospective study included 237 patients aged 16 to 40 years, with an average of 27.3. The patients were categorized into three different age groups, under 20 years, between 20 and 30 years, and between 30 and 40 years. Depending on the values of the angle of the long axis of the lower third molar with the axis of the mandibular canal we divided the cases into three groups: the first with an angle of 0°-30°, the second with an angle between 30°-60° and the last with values between 60°-90°. Another studied parameter was the operating time. Results: There were 67 patients under 20 years old (28.3%), 113 between 20 and 30 (47.7%), and (24%) between 30 and 40. 35% of the group were men, while 65% were women. The chi-square test showed a negative correlation between the duration of the surgical intervention and the molar angulation (p=0.049). There was no statistically significant correlation between the duration of the extraction and the age of the patients (p=0.941).Conclusion: Based on the results of our study, we can propose a larger one to confirm the findings of your research.